Evaluation of performance parameters in conventional reactor: application in industrial processes (Research, Society and Development, 2019)
When a stirring and mixing system is not correctly designed and controlled, undesirable mixtures are obtained, which can lead to product losses and increased process costs. Therefore, the objective of this study is to evaluate a system of agitation and mixing that can generate experimental data for the aid of researchers and designers of industrial impellers. This system was evaluated using four different configurations of impellers (Rushton-Rushton; Rushton-Smith; Smith-Rushton and Smith-Smith) based on two fundamental performance parameters of the stirring system: mixing time and energy consumption. The mixing time was determined by temperature pulse method and the calculation of the power consumption was obtained from the literature equations. The performance parameters were evaluated in three different rotation frequencies: 300, 500 and 700 rpm. The configuration (4) showed a reduction in the mixing time of 36% (300 rpm), 63% (500 rpm) and 79% (700 rpm) when compared to the standard configuration (1). From the obtained results, it was possible to conclude that the configuration (4), obtained the lowest mixing time and lower power consumption of all the configurations evaluated. In addition, it can be determined that the stirring frequency of 500 rpm was the most adequate for this study.